2012
DOI: 10.1073/pnas.1207787109
|View full text |Cite
|
Sign up to set email alerts
|

cAMP response element-binding protein promotes gliomagenesis by modulating the expression of oncogenic microRNA-23a

Abstract: Gliomas are the most common and deadly type of primary brain tumor. In this study, we showed that cAMP response element-binding protein (CREB), a proto-oncogenic transcription factor that is overexpressed in gliomas, can promote gliomagenesis by modulating the expression of oncogenic microRNA-23a (mir-23a). First, we found that CREB is highly expressed in glioma tissues and cell lines. CREB is also essential for glioma cell growth and cell survival in vitro and is critical for gliomagenesis in vivo. Second, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
88
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 48 publications
5
88
0
Order By: Relevance
“…These data are in line with recent studies demonstrating that CREB knockdown reduces cell survival and proliferation, and cell-cycle progression of different tumor cells (37)(38)(39), and they were further strengthened by the rescue of CREB expression in the shCREB-HER-2/neu þ cells, which reversed the untransformed morphology and growth characteristics (Fig. 2).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These data are in line with recent studies demonstrating that CREB knockdown reduces cell survival and proliferation, and cell-cycle progression of different tumor cells (37)(38)(39), and they were further strengthened by the rescue of CREB expression in the shCREB-HER-2/neu þ cells, which reversed the untransformed morphology and growth characteristics (Fig. 2).…”
supporting
confidence: 91%
“…The reduced invasion potential and enhanced apoptotic activity in vitro was confirmed by the significant decrease and delayed tumor growth of the shCREB-HER-2/neu þ cells in vivo. These data are in line with results from a nude-mouse model in which the mice were injected with melanoma cells expressing dominant-negative CREB (12), in glioma cells transfected with shCREB (39), and in an artificial CREB model in which CREB Ser133 is mutated (53). Furthermore, the first own results analyzing the frequency of immune cells upon in vivo application of HER-2/neu þ cells and their counterpart shCREB-HER-2/neu þ cells suggest that CREB silencing also affects the immunogenicity of tumors and the antitumor immune response, which is currently being investigated in detail.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, in human glioblastoma cell lines, CREB small interfering RNA treatment decreases miR-21 expression. 34 However, whether CREB directly regulates miR-21 promoter activity is not known. We have determined that CREB physically binds to the miR-21 promoter in mouse kidney cells, and mutating CREB binding sites or inhibiting cAMP signaling reduces the transcriptional activity of miR-21 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that elevated level of miR-23a in OLs is sufficient to promote formation of myelin that can last until older age (at least 1-y old) partly through the Akt/mTOR and MAPK signaling pathways by targeting PTEN. A recent study reported that the cAMP-response element-binding protein (CREB) promotes glioma formation by up-regulating miR-23a, leading to down-regulation of its direct target, PTEN (29). Thus far, we have not observed obviously increased incidence of glioma formation in murine brains overexpressing miR-23a in myelinating glia.…”
Section: Discussionmentioning
confidence: 53%